2003
DOI: 10.1177/026142940301800107
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Nomination: German Version of the Scales for Rating the Behavioral Characteristics of Superior Students

Abstract: Teacher nomination is often used as one criterion of a multidimensional approach towards identifying students with high abilities. Multiple criteria can be useful to identify students for gifted programs who may be overlooked using traditional methods. The teacher rating scales discussed in this study have been extensively used in the United States and have been translated into twelve other languages for use in identification of talented students in other countries. The purpose of this study was to develop tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…With that in mind, Burke et al (1982) concluded that their findings regarding the factorial structure of the SRBCSS are not entirely consistent with Renzulli et al (1976). Rogalla (2003) developed a German version of the SRBCSS revised (SRBCSS-R) based on teacher nominations of talented students for enrichment programs in the German-speaking part of Switzerland. Within the context of construct validation, SRBCSS-R was completed on 572 students enrolled at various grades from 3 to 12 on four meaningful subscales: learning, creativity, motivation, and communication.…”
Section: Srbcss: Development and Validationmentioning
confidence: 99%
“…With that in mind, Burke et al (1982) concluded that their findings regarding the factorial structure of the SRBCSS are not entirely consistent with Renzulli et al (1976). Rogalla (2003) developed a German version of the SRBCSS revised (SRBCSS-R) based on teacher nominations of talented students for enrichment programs in the German-speaking part of Switzerland. Within the context of construct validation, SRBCSS-R was completed on 572 students enrolled at various grades from 3 to 12 on four meaningful subscales: learning, creativity, motivation, and communication.…”
Section: Srbcss: Development and Validationmentioning
confidence: 99%
“…Scales for Rating the Behavioral Characteristics of Superior Students (SRBCSS) (Renzulli, Smith, White, Callahan, Hartman, Westberg, Gavin, Reis, Siegle & Sytsma, 2010).…”
Section: Renzulli Scale Of Behavioral Characteristicsmentioning
confidence: 99%
“…Speaking about the scale, In 1990, Karen Westberg reformulated four genderneutral domains, obtained high reliability and compared to teacher nominations, and was published in 2002. The scale includes the following domains: learning, creativity, motivation, leadership, arts, music, drama , Communication, communication (expression), planning (Renzulli et al, 2010).…”
Section: Renzulli Scale Of Behavioral Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations